An open labelled randomized clinical trial of fluoxetine versus dapoxetine treatment among men with premature ejaculation and its effect on marital satisfaction - Man, Mohamad Hj Che' (2016)
INTRODUCTION: Premature ejaculation (PE) causes reduces sexual satisfaction and quality of life. Both Selective Serotonin Re-uptake Inhibitor Fluoxetine and Dapoxetine have been used in treatment of PE. Fluoxetine is used as off-label treatment meanwhile Dapoxetine is the first SSRI specifically designed for PE that has a short half-life and few side effects. OBJECTIVES: To compare the PE symptoms score and marital satisfaction score between Fluoxetine and Dapoxetine groups. METHODS: In this open labelled randomized clinical trial, 44 participants aged between 18 and 64 with PEDT score of ≥ 9 from the Primary Care clinic of Hospital USM, Kelantan Malaysia were recruited and randomized into two groups; Fluoxetine Group (FG) and Dapoxetine Group (DG). They were prescribed with either daily oral Fluoxetine 20mg or Dapoxetine 30mg on demand twice weekly for 8 weeks. PE symptoms were measured using the Premature Ejaculation Diagnostics Tool (PEDT) score and marital satisfaction score were measured using the Dyadic Satisfaction-Dyadic Adjustment Scale (DS-DAS) score. Measurements were made at baseline and at the 8th week (post intervention). RESULTS: In FG and DG, 22 and 21 participants completed the study, respectively. PEDT scores reduced significantly within both groups [from 11.41 to 5.45 (P<0.001) within FG and from 13.43 to 3.10 (P<0.001) within the DG]. At the 8th week follow-up, PEDT scores was observed to be were lower in DG (6.03 vs. 2.49, P<0.001) after adjustment of the baseline PEDT score. Significantly increased DS-DAS scores were observed in both groups [from34.50 to 40.68 (P<0.001) within FG and from 36.57 to 44.33, (P<0.001) within DG] with no significant difference in DS-DAS scores at the end of study (41.13 vs. 43.86, P=0.055) after adjustment of the baseline DS-DAS score. CONCLUSIONS: Reduction in PE symptoms was observed for both groups. At 8 weeks, PE symptoms among participants on Dapoxetine were significantly lower compared to the participants on Fluoxetine group at 8 weeks. Treatment of PE with either Fluoxetine or Dapoxetine reduces symptoms of PE and improves marital satisfaction.